The Rich Get Richer: Osseous Chimeric Versatility to the Anterolateral Thigh Flap - Yu, Jason W.; Frey, Jordan D.; Thanik, Vishal D.; Rodriguez, Eduardo D.; Levine, Jamie P. (Journal of Reconstructive Microsurgery, 2020)
Background The lateral femoral circumflex artery (LFCA) system, which supplies the anterolateral thigh (ALT) flap territory, offers a plethora of tissue types for composite, functional reconstruction. However, the ability to include a reliable and flexible osseous component is limited. Based on cadaveric dissections, we describe an isolated LFCA branch to the femur separate from the vastus intermedius that can be included in ALT flap harvest in cases requiring bony reconstruction.Methods Cadaveric dissection was undertaken to define the LFCA vascular system with specific dissection of the proximal branches of the descending branch of the LFCA (db-LFCA) to define any muscular, periosteal, and/or osseous branches to the femur.Results Six thighs in four cadavers were dissected. Consistent in all specimens, there was an isolated branch extending distally, medially, and posteriorly from the proximal LFCA and entering the periosteum of the femur. In five specimens, the identified branch to the femur was located approximately 1-cm distal to the rectus femoris branch of the LFCA and approximately 1-cm proximal to a separate branch entering and supplying the vastus intermedius. In one specimen, there was a common trunk. The length of this branch from the origin at the LFCA to insertion into the femoral periosteum was approximately 6 to 8 cm.Conclusion There appears to be a consistent and reliable branch to the femur based on the proximal LFCA that may be included in ALT flap harvest, adding even more versatility, as another option in complex cases requiring composite reconstruction, including bone.
Keywords: anterolateral thigh flap; chimeric osseous flap; lateral femoral circumflex artery